Efektivitas Terapi pada Gangguan Kecemasan - Hasanah, Mielosita; Hairy, Fathinah Salsabilla; Nursiain, Aziza Chantiqka Aulia; Ananda, Asti (LPPM Universitas Mataram, 2025)
Anxiety disorders are psychological conditions characterized by excessive and pathological anxiety or worry, and they remain a significant mental health concern in both developed and developing countries. Managing these disorders requires effective therapeutic interventions, both psychological and pharmacological. This article reviews various therapeutic approaches used in the treatment of anxiety disorders, including cognitive behavioral therapy (CBT), dialectical behavior therapy (DBT), supportive therapies, and pharmacological treatments. The review focuses on the effectiveness, mechanisms of action, and factors influencing the success of each therapy. Findings indicate that CBT consistently demonstrates high effectiveness in reducing symptoms across different types of anxiety disorders. Appropriate and comprehensive therapy selection based on individual conditions is essential to improve clinical outcomes and patient prognosis.